PENERAPAN MODEL NATURE LEARNING DALAM PEMBELAJARAN MENULIS TEKS PUISI PADA SISWA KELAS X MAN 1 INDRAMAYU - Untiyana, Ginnas; Subaweh, Ahmad Maskur; Khoirul Fajri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Poetry is a type of literary work that expresses feelings, thoughts and experiences in beautiful and structured language. In learning to write poetry, students will be taught material regarding language styles, so that the poetry they write is more interesting and beautiful. This research is motivated by learning models that are still lacking in variety, lack of student ability, and student inactivity in learning to write poetry texts. The aim of this research is to see the effectiveness of the nature learning model in learning to write poetry texts. The research method used in this research is an experimental study with research subjects, namely 28 class X-1 students as the control class and 27 class X-2 students as the experimental class. The method for collecting data in this research is by collecting data from observations and tests (pretest and posttest). Based on the results of statistical calculations using the independent samples t test, the tcount was 2.825 and the ttable was 1.693. So tcount 2.825 > ttable 1.693, this shows that H0 is rejected and H1 is accepted.